2021
DOI: 10.3389/fimmu.2021.718841
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 23 Produced by Hepatic Monocyte-Derived Macrophages Is Essential for the Development of Murine Primary Biliary Cholangitis

Abstract: Background and AimsPrimary Biliary Cholangitis (PBC) is an organ-specific autoimmune liver disease. Mononuclear phagocytes (MNPs), comprise of monocyte, dendritic cells and monocyte-derived macrophages, constitute major arm of the innate immune system known to be involved in the pathogenesis of autoimmune disorders. MNPs were shown to accumulate around intra-hepatic bile ducts in livers of PBC patients. Interleukin 23 (IL-23) is a pro-inflammatory cytokine. IL-23-positive cells were detected in livers of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…IL-23 was significantly higher (hepatic blood, p ¼ 0:04) in patients with decompensated cirrhosis. This is an interesting finding because IL-23 can be produced by hepatic monocyte-derived macrophages, corroborating that myeloid cells fuel systemic inflammation in decompensated cirrhosis [21,35,36].…”
Section: Discussionsupporting
confidence: 53%
“…IL-23 was significantly higher (hepatic blood, p ¼ 0:04) in patients with decompensated cirrhosis. This is an interesting finding because IL-23 can be produced by hepatic monocyte-derived macrophages, corroborating that myeloid cells fuel systemic inflammation in decompensated cirrhosis [21,35,36].…”
Section: Discussionsupporting
confidence: 53%
“…Hepatic macrophages have been implicated in the pathogenesis of murine autoimmune cholangitis [ 45 ]. Macrophages were affected by the JAK1 selective kinase inhibitor and pan-JAK inhibitor tofacitinib in an experimental colitis model [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…At present, little is known concerning the functional mechanism of IL23R in the development of CHOL. However, it was reported that IL-23 produced by macrophages derived from liver monocytes plays a major role in the pathogenesis of primary biliary cirrhosis ( 44 ), which is one of the main risk factors of CHOL ( 45 ). These and similar findings point to productive research directions in CHOL, especially related to the PI3K-Akt signaling pathway, immune-related TME, and amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%